E.S. Dallas elsewhere
1 online resource (436 pages)
Keywords: Providing a collection of E.S. Dallas's work, this volume explores the significance of the Scottish writer's practical and theoretical contributions to both the criticism and journalism of the mid-nineteenth century, as well as offering an edited selection of Dallas's writings in the Victorian press. This book provides a comprehensive listing of around 250 contributions to other periodicals, and again offer a generous edited selection of around 40 articles that are representative of this body of work as a whole. The source materials were published between the summer of 1850, just after Dallas left Edinburgh University, and early 1881 when a posthumous article appeared two years after his death; they appeared in periodicals issued daily, weekly, monthly, quarterly and even annually, in both Edinburgh and London; and generically, they range from book reviews both literary and non-literary, coverage of theatrical and other performances, articles on a cornucopia of social, cultural and philosophical issues, and reports from Paris as special correspondent both during and after the Franco-Prussian War.